2019
DOI: 10.1177/1059601119834093
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Work Motivation Conceptualization of Grit in Organizations

Abstract: Despite its widespread media acclaim and recognition as a strategic imperative, the role of grit in organizational research remains unclear. This ambiguity resulted from inconsistent empirical findings, thus triggering a pessimistic outlook for the construct across disciplines. To address these issues, we suggest that such confusion and lack of construct and predictive validity stem from not only methodological issues but also a lack of theoretical sophistication. In this article, we address methodological iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 179 publications
(243 reference statements)
0
79
0
1
Order By: Relevance
“…Grit is positioned as a vital personal resource required to translate individual drive and resolve, into measurable performance outcomes on both an individual and organizational level (Nelson and Baltes, 2019). Previous studies reported a direct and positive relationship between grit and various permutations of performance ranging from academic success/performance (Duckworth and Quinn, 2009;Jachimowicz et al, 2018;Nelson and Baltes, 2019), and training performance in sports (Cazayoux and DeBeliso, 2019), to job performance (Jordan et al, 2019;Kim et al, 2019;Webster-Wright, 2019), operational productivity (Steuber et al, 2019), and even task performance (Vogelsang, 2018). Koopmans et al (2013) argued that task performance seems to be an important indicator of operational efficiency and personal performance, which is also strongly influenced by non-cognitive traits such as personality, interest and drive.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Grit is positioned as a vital personal resource required to translate individual drive and resolve, into measurable performance outcomes on both an individual and organizational level (Nelson and Baltes, 2019). Previous studies reported a direct and positive relationship between grit and various permutations of performance ranging from academic success/performance (Duckworth and Quinn, 2009;Jachimowicz et al, 2018;Nelson and Baltes, 2019), and training performance in sports (Cazayoux and DeBeliso, 2019), to job performance (Jordan et al, 2019;Kim et al, 2019;Webster-Wright, 2019), operational productivity (Steuber et al, 2019), and even task performance (Vogelsang, 2018). Koopmans et al (2013) argued that task performance seems to be an important indicator of operational efficiency and personal performance, which is also strongly influenced by non-cognitive traits such as personality, interest and drive.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…For instance, the most frequently used measure of grit (Duckworth and Quinn 2009 ) includes only one goal-related item (i.e., “I often set a goal but later choose to pursue a different one.”). This lack of goal-related items not only raises concerns about conceptualization and measurement (Credé 2018 ), but it also hinders the ability of researchers to identify the strength of grit effects (Jordan et al 2019 ). According to goal-setting theory (Locke and Latham 2002 ), successful goal pursuit requires two effective elements: goal setting and goal implementation (Kruglanski et al 2015 ; Oettingen and Gollwitzer 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent re-conceptualizations of grit have identified this contextualized goal-grit-achievement issue as the main reason behind the low associations between grit and achievement. According to Jordan et al ( 2019 ), grit should be regarded as the context-specific ability to (a) set and pursue long-term goals and (b) readjust short-term goals and goal attainment strategies in the face of challenges and difficulties. Thus, without information on goals and their contents, grit is an undirected energy that is easily drained (Jordan et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grit, a relatively new construct in the behavioural sciences that has received a lot of attention recently [2], is defined as perseverance and passion for long-term goals [3].…”
Section: Introductionmentioning
confidence: 99%